The Use of Neurovascularized Flaps in Plastic Surgery of Gunshot Defects of the Hindfoot - Strafun, S.S.; Shypunov, V.H.; Borzykh, N.O.; Zahovenko , M.A. (TERRA ORTHOPAEDICA, 2024)
Summary. Background. Gunshot fractures of the bones of the foot make up 12% of the total number of injuries of the lower extremities and in 37% of cases are accompanied by a defect in the tissues of the foot, which is considered as a predictor of amputations at the level of the lower leg. Restoring the function of foot support is possible only when reconstructive plastic surgery – neurovascularized flaps – is performed. Objective: to study the frequency of ischemic complications of flaps during plastic surgery of extensive defects of soft tissues of the rear part of the foot with “sural” and “plantar” flaps in the case of gunshot polystructural injuries of the foot. Materials and Methods. A retrospective analysis of the treatment of 43 injured with gunshot extensive defects of the soft tissues of the hindfoot from 2014 to 2023 and at different times of injury was carried out: up to 3 days – 10 cases; from 3 to 10 days – 22 cases; from 10 to 20 days – 11 cases. In 23 (53%) cases there was a defect of the loading surface of the heel area. In 20 (47%) cases there was a defect of the posterior, non-load-bearing surface of the heel area, which in 3 (7%) cases was accompanied by damage to the Achilles tendon. In 27 (63%) cases, the tissue defect was combined with a foot bone fracture: calcaneal bone – 4 (9.3%), calcaneus and tarsal bone – 3 (6.9%), calcaneus and metatarsal bone – 4 (9.3%). The decision regarding the use of the type of flap for plastic surgery of the soft tissue defect of the hindfoot depended on the location of the defect and the results of instrumental examination. Doppler imaging was performed to determine blood flow in the medial plantar artery and in the basin of the small and great saphenous veins, and to determine the presence of a perforator of the peroneal artery. Results. The assessment of the development of ischemic complications of the “sural” and “plantar” flaps was carried out during the first 10 days. Complications associated with a violation of blood supply of flaps occur in 18.6% of cases. The “sural” flap compared to the “plantar” flap is more prone to ischemic complications (21% versus 14%). Conclusions. The use of neurovascularized flaps in plastic surgery of soft tissue defects of the foot makes it possible to cover large defects without the involvement of microsurgery. In some cases, the surgery is accompanied by the development of irreversible ischemic changes. Nevertheless, performing such surgeries makes it possible to save the foot and buy time before making a decision for amputation.